2017
DOI: 10.1016/j.ahj.2016.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise and stress management training on nighttime blood pressure dipping in patients with coronary heart disease: A randomized, controlled trial

Abstract: INTRODUCTION Blunted nighttime blood pressure (BP) dipping is prognostic of cardiovascular morbidity and mortality. Patients with coronary heart disease (CHD) are often characterized by a blunted nighttime BP dipping pattern. The present study compared the effects of two behavioral intervention programs, aerobic exercise (EX) and stress management (SM) training, with a usual care (UC) control group on BP dipping in a sample of CHD patients. METHODS This was a secondary analysis of a randomized controlled tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Finally, with regard to changes in the magnitude of BP dipping in nondippers, we observed these individuals increased BP dipping after the intervention. This finding aligns with previous studies and demonstrates that exercise may improve BP dipping profile, even when daytime and nighttime systolic BP remain unchanged ( Ling et al, 2014 ; Sherwood, Smith, Hinderliter, Georgiades, & Blumenthal, 2016 ).…”
Section: Discussionsupporting
confidence: 93%
“…Finally, with regard to changes in the magnitude of BP dipping in nondippers, we observed these individuals increased BP dipping after the intervention. This finding aligns with previous studies and demonstrates that exercise may improve BP dipping profile, even when daytime and nighttime systolic BP remain unchanged ( Ling et al, 2014 ; Sherwood, Smith, Hinderliter, Georgiades, & Blumenthal, 2016 ).…”
Section: Discussionsupporting
confidence: 93%
“…It has long been known that physical exercise confers many beneficial effects on health. Studies demonstrate that exercise improves cardiovascular function [ 56 ], cognitive ability [ 27 ], and insulin resistance and symptoms of metabolic syndrome [ 57 ] and decreases the severity of neuropsychiatric problems, including depression [ 58 ]. Di Loreto et al demonstrated that regular physical activity potently augmented neuroprotective functions as a correlate of age-related amyloidogenesis and additionally preserved synaptic function [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Exercise training could reduce two of the key features of elevated nighttime BP, which are sympathetic nervous system and RAAS over activity [9]. However, the information on the effects of aerobic exercise training on nocturnal BP dipping in hypertensive population is meager and contradictory, with studies finding a dipping effect [10,11], whereas others failed to find an effect [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Sherwood et al . [11] found in coronary heart disease patients that aerobic exercise training improved nighttime BP dipping compared with usual medical care. However, Nami et al .…”
Section: Discussionmentioning
confidence: 99%